2007
DOI: 10.1007/s10646-007-0147-z
|View full text |Cite
|
Sign up to set email alerts
|

Embryotoxic effects of nonylphenol and octylphenol in sea urchin Arbacia lixula

Abstract: Nonylphenol (NP) and octylphenol (OP), both of which are biodegradation products of alkylphenols, are widely used in industrial applications and in some domestic products. These chemicals are found widely in surface water and aquatic sediments. We have carried out a comparative embryotoxicity analysis of the effects of increasing concentrations of NP (seven concentrations ranging from 0.937 to 18.74 microg/l) and OP (six concentrations ranging from 5 to 160 microg/l) on embryos of the sea urchin Arbacia lixula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…For example, it was observed that environmental concentration of several pharmaceuticals can affect the regeneration of Hydra attenuata (cnidarian) (Quinn et al, 2008a(Quinn et al, , 2008b; triclosan at this range can produce genotoxic and cytotoxic effects in Dreissena polymorpha (mussel) (Binelli et al, 2009a). In addition, teratogenic effects have been recorded in sea urchins Arbacia lixula exposed to atenolol (Karaaslan et al, 2012) and in Strongylocentrotus purpuratus exposed to an environmental concentration of tamoxifen (Roepke et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was observed that environmental concentration of several pharmaceuticals can affect the regeneration of Hydra attenuata (cnidarian) (Quinn et al, 2008a(Quinn et al, , 2008b; triclosan at this range can produce genotoxic and cytotoxic effects in Dreissena polymorpha (mussel) (Binelli et al, 2009a). In addition, teratogenic effects have been recorded in sea urchins Arbacia lixula exposed to atenolol (Karaaslan et al, 2012) and in Strongylocentrotus purpuratus exposed to an environmental concentration of tamoxifen (Roepke et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Sea urchins are recognized as an excellent model system for eco-embryo-and geno-toxicological studies (Geraci et al 2004;Bonaventura et al 2005;Cakal Arslan and Parlak 2007;Bellas et al 2008b;Nahon et al 2008). Stress proteins play a critical role in a complex defence mechanism, enhancing cell survival under adverse environmental conditions as well as in normal cellular homeostasis (Diller 2006).…”
Section: Introductionmentioning
confidence: 99%
“…2006;Venkatesan and Halden 2013). NP present in the environment is mainly derived from nonylphenol ethoxylates (NPEs) which are nonionic surfactants that are used in a wide range of industrial processes and consumer products (Arslan and Parlak 2007). NPEs is discharged in sewage water and are then converted into NP, which is more persistent and poisonous than NPEs and accumulates in sewage sludge (Capota et al 2004;Fountoulakis et al 2005;Kim et al 2007;Arditsoglou and Voutsa 2008;Zhang et al 2008).…”
Section: Introductionmentioning
confidence: 99%